Effect of Leishmania proteins in mice: Investigation of Leishmania amazonensis virulence molecules for therapy and prophylaxis of leishmaniasis - Araújo, Cintia Figueiredo de; Andrade, Candace Machado; Khouri, Mariana Ivo; Andrade, André Cronemberger; Aragão-França, Luciana Souza de; Rocha, Viviane Costa Junqueira; Silva, Virgínia Maria Góes da; Carvalho, Lain Carlos Pontes de (Acta Scientiarum. Biological Sciences, 2025)
It has been reported that a single injection of Leishmania amazonensis amastigote extract (LaE) in BALB/c mice exacerbates the infection of these animals with Leishmania braziliensis. This study aimed to investigate proteins of LaE that confers susceptibility to L. braziliensis infection. Methods BALB/c mice were injected with saline, LaE, isolate fractions of the LaE (68, 45, 36, and 28 kDa), or L. infantum recombinant protein Lci1 (Hsp70). After a week, the animals were infected with L. braziliensis, and the lesion’s size was monitored weekly. Six weeks later, the parasite burden in the footpads and the activities of IgG1 and IgG2a anti-LaE antibodies were determined. Additionally, the 68 and 28 kDa fractions were supplemented with serine and cysteine protease inhibitors and evaluated in the same described experimental model. The intradermal injection of BALB/c mice with 68, 36, and 28 kDa fractions of LaE, and the recombinant protein Lci1 conferred significant susceptibility to L. braziliensis infection, but not the 45 kDa fraction. This potentiating effect was associated with the increase in increment of the lesion size, parasite load, and IgG1 anti-LaE antibodies. Furthermore, the biological activity of the 68 and 28 kDa fractions was inhibited by the pretreatment of the extract with serine protease inhibitors. Our study found the biological activity of the 68, 36, and 28 kDa fractions, as well as the recombinant protein Lci1, exacerbating the infection in our experimental model.